The role of dorsal raphe nucleus neuropeptides in reward and aversion - Braden, Kathryn; Castro, Daniel C. (Frontiers in Behavioral Neuroscience, 2025)
The dorsal raphe nucleus is a critical node for affective and motivated circuits in the brain. Though typically known as a serotonergic hub, the dorsal raphe nucleus is also highly enriched in a variety of neuropeptides. Recent advances in biotechnology and behavioral modeling have led to a resurgence in neuropeptide research, allowing investigators to target unique peptide systems with unprecedented clarity. Here, we review and discuss multiple neuropeptide systems in dorsal raphe and consider how their activity may contribute to reward and aversion. While this is not an exhaustive review, this short overview will highlight the many opportunities available to refine our understanding of multiple dorsal raphe neuropeptides. By more thoroughly studying dorsal raphe neuropeptides, we will reveal novel pathways to design more effective therapeutics and tailor treatments for millions of patients.